Answer:
- 1
Explanation:
z₁ - z₂ = 1 - i - (- 2 + 4i) = 1 - i + 2 - 4i = 3 - 5i, thus
![(3-5i)/(1-i)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/d22dydwxaj50gcip3ssk4oo7k0auxqrzmw.png)
Rationalise the denominator by multiplying the numerator/denominator by the complex conjugate of the denominator
The conjugate of 1 - i is 1 + i, so
![((3-5i)(1+i))/((1-i)(1+i))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/q7iemc0slwnkgp3ciki76u56lx7jppp7n1.png)
expand numerator / denominator noting i² = - 1
=
![(3-2i-5i^2)/(1-i^2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4v4p7y34fjmm7n154n832glmolbgsyrcaq.png)
=
![(3-2i+5)/(1+1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zm1d9awxexl0ufsge19u9urqq1opqo27cc.png)
=
![(8-2i)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xfqc2939096l39ljpxgtmjsawkq9qrdteh.png)
= 4 - i
Thus Im [
] = - 1